A wave of support? A natural experiment on how the COVID-19 pandemic affected the popularity of a basic income - Arno Van Hootegem; Tijs Laenen (Acta Politica, 2022)
Although a basic income (BI) has already been widely debated, the COVID-19 crisis further intensified the discussion about this periodic cash payment that is unconditionally delivered to all. However, it remains unclear whether the crisis spurred a wave of public support for its introduction. To investigate this, we aim to answer two research questions: (1) How did support for a BI evolve in reaction to the COVID-19 crisis? and (2) To what extent did the evolution in support differ across regional contexts and social groups with varying levels of deprivation? We rely on a natural experiment by analysing data from the Belgian National Elections Study that was collected both before and during the pandemic. The results indicate an increase in support for a BI due to the pandemic, although it seems short lived and not necessarily specific to a BI. Importantly, however, the increase in popularity is only observable in the high-unemployment French-speaking region of Belgium and among relatively deprived groups.
Keywords: 320; public preferences; basic income; COVID-19 pandemic; polarization; natural experiment